How Does Context Affect The Professionalism of Dakwah of M.Natsir In Indonesian Islamic Dakwah Council: A Pragmatics Point of View - Jarudin, Jarudin; Kemal, Edwar; Nasir, Badlihisham Mohd; Azlan, Ulfatmi (ppjbsip, 2023)
M. Natsir is one of the community leaders who is considered a multidimensional figure whose personality, abilities and expertise are very limited. History records that his struggle is always dynamic and gives the best for the Indonesian people and the Islamic religion. This study discusses how the context influences the professionalism of Muhammad Natsir's preaching in the Indonesian Islamic Da'wah Council. This study uses a qualitative descriptive method with a library research research design. Data was collected using storage techniques sourced from readings/texts and books. Furthermore, the data were analyzed using content analysis method. The results of the study show that M. Natsir is an influential and professional figure in his field, especially in the field of Islam and da'wah. From the internal context it was found that the influence of the family environment, educational background and understanding of religion was evident from his involvement in various important government positions, as well as various organizations including the Indonesian Islamic Da'wah Council. From the external context it was found that M.Natsir's involvement in da'wah work programs to various regions, cadre of qualified preachers through mosques, campuses and Islamic boarding schools, dispatched preachers for even distribution of the reach of da'wah messages. and the fourth; publishing as an effort to provide or entertain what is felt by the Islamic community in the field of literature.